Potential Nephroprotective Effect of Kaempferol: Biosynthesis, Mechanisms of Action, and Clinical Prospects - Maulana Yusuf Alkandahri; Asman Sadino; Barolym Tri Pamungkas; Zulpakor Oktoba; Maya Arfania; Nia Yuniarsih; Eko Sri Wahyuningsih; Yuliani Dewi; Sri Ayu Winarti; Sri Tantia Dinita (Hindawi Limited, 2024)
Kidney is an essential organ that is highly susceptible to cellular injury caused by various toxic substances in the blood. Several studies have shown that untreated injuries to this organ can cause glomerulosclerosis, tubulointerstitial fibrosis, and tubular cell apoptosis, leading to kidney failure. Despite significant advancements in modern treatment, there is no fully effective drug for repairing its function, providing complete protection, and assisting in cell regeneration. Furthermore, some available medications have been reported to exacerbate injuries, showing the need to explore alternative treatments. Natural drugs are currently being explored as a new therapeutic strategy for managing kidney diseases. Kaempferol, a polyphenol found in plants, including vegetables, legumes, and fruits, has been extensively studied in various nephrotoxicity protocols. The compound has been reported to have potential as a nephroprotective agent with beneficial effects on various physiological pathways, such as CPL-induced kidney injury, DOX, LPO, ROS, RCC, and diabetic nephropathy. Therefore, this study aims to provide a brief overview of the current nephroprotective effects of kaempferol, as well as its molecular mechanisms of action, biosynthesis pathways, and clinical prospects.